Differential proxy responses to late Allerød and early Younger Dryas climatic change recorded in varved sediments of the Trzechowskie palaeolake in Northern Poland. (15th February 2017) - Słowiński, Michał; Zawiska, Izabela; Ott, Florian; Noryśkiewicz, Agnieszka M.; Plessen, Birgit; Apolinarska, Karina; Rzodkiewicz, Monika; Michczyńska, Danuta J.; Wulf, Sabine; Skubała, Piotr; Kordowski, Jarosław; Błaszkiewicz, Mirosław; et al.
Abstract: High-resolution biological proxies (pollen, macrofossils, Cladocera and diatoms), geochemical data (μ-XRF element scans, TOC, C/N ratios, δ 18 Ocarb and δ 13 Corg values) and a robust chronology based on varve counting, AMS 14 C dating and tephrochronology were applied to reconstruct lake system responses to rapid climatic and environmental changes of the Trzechowskie palaeolake (TRZ; Northern Poland) during the late Allerød – Younger Dryas (YD) transition. Palaeoecological and geochemical data at 5–15 years temporal resolution allowed tracing the dynamics of short-term shifts of the ecosystem triggered by abrupt climate change. The robust age control together with the high-resolution sampling allowed the detection of leads and lags between different proxies to the climate shift at the Allerød-Younger Dryas transition. Our results indicate (1) a water level decrease and an increase in wind activities during the late Allerød and the Allerød-YD transition, which caused intensified erosion in the catchment, (2) a two-decades delayed vegetation response in comparison to the lake depositional system. Comparison with the Lake Meerfelder Maar record revealed slightly different vegetation responses of the Trzechowskie palaeolake at the YD onset. Highlights: High-resolution biological proxies (pollen, macrofossils, Cladocera and diatoms) and geochemical data. Robust chronology based on varve counting, AMS 14 C dating and tephrochronology. Palaeoecological and geochemical data at 5–15 years temporal resolution. Reconstruction lake system responses to rapid climatic and environmental changes during the late Allerød – Younger.